Perancangan Ulang Tata Letak Fasilitas Pabrik (Re-Layout) PT.XYZ - Handi Wilujeng Nugroho (Journal of Engineering Science and Technology Management (JES-TM), 2022)
The company is a medium scale company, although the medium scale company has used modern equipment. Such as lathes, milling machines, hydraulic press machines, iron cutting machines (benso), iron/steel plate press machines, steel/iron bending machines and others. Meanwhile, the arrangement of stations or existing production machines is still irregular and causes the production floor to be scattered and ineffective as well as inefficient spatial planning in the production process so that this affects the operator, maximizing output and time. The research method is carried out with systematic steps that are arranged and determined before solving the problem. The initial research stage is calculating the utility of the distance between stations and machines using ARC and ARD, then making improvements to the layout from the initial layout in order to achieve the research objectives. The purpose of this study is to propose an efficient layout and flow of material handling in order to reduce time in the tailgate production process. The number of departments or rooms, namely 12 departments needed in planning the linkage of activities, namely production room, storage room, rest room and first aid kit, generator room, office space, private motorbike and car parking, truck and trailer truck parking, drying area, truck unloading area, Places of Worship, Security Post, and Toilets.